Method of closing fasciotomies by progressive tissue traction - Antoninho José Tonatto; Jorge Luís de Moraes; Caio Munaretto Giacomazzo; Bruna Valduga Dutra; José Paulo Tapie Barbosa; Renato da Silva Freitas (Revista Brasileira de Cirurgia Plástica, 2023)
High-energy trauma has increased significantly in the last decade, mostly in the lower limbs, in many cases requiring fasciotomy due to the subsequent compartment syndrome. In this context, its closure often leads to a delay in the patient’s comprehensive treatment and the return to their activities and may lead to local infection, in addition to generating high costs. There are many options for the plastic surgeon to try to bring the edges together and reconstruct the extremities, such as flaps, grafts, vacuum dressings, and elastic sutures, in addition to expansion devices, sometimes with a combination of the above.